Effect of micronutrients-enriched fertilizers on basal stem rot disease incidence and severity on oil palm (Elaeis guineensis Jacq.) seedlings - Tengoua, Fabien Fonguimgo; Musa, Mohamed Hanafi; Abu Seman, Idris; Kadir, Jugah; Jamaludin, Nurul Mayzaitul Azwa; Mohidin, Hasmah; Syed Rastan, Syed Omar (Science Publications, 2014)
Basal stem rot caused by Ganoderma boninense constitutes a serious threat to oil palm industry in Southeast Asia, especially in Malaysia and Indonesia and in Papua New Guinea and Pacific Islands. It is also expanding in some oil palm growing countries in Latin America and Africa and will soon become a worldwide concern to oil palm cultivation. To date, none of the various control measures developed and tested to control the disease since many decade gives entire satisfaction. An experiment was carried out to see whether incorporation of micronutrients, Copper (Cu), Boron (B) and Manganese (Mn) could reduce the incidence and severity of this disease on oil palm seedlings inoculated with G. boninense. The concentrations tested were 2 mg B/kg of soil, 2 mg Cu/kg of soil and 2 mg Mn/kg of soil incorporated into the basic fertilizer NPKMg 14-10-10-2. Treatments were applied in solution for three months before inoculation, followed by soil application for eight months after inoculation. The results showed that although no significant difference was detected among treatments, the double combinations of these micronutrients, B+Cu, B+Mn and Cu+Mn, performed better than the single nutrients in reducing the incidence and the severity of BSR, while their triple combination rather increased these pathological parameters. These double combinations could therefore be field-tested for their further integration in oil palm fertilization programme.